Pharmacokinetic and pharmacodynamic responses in adult patients with Chagas disease treated with a new formulation of benznidazole - Marisa Fernández; María Elena Marsón; Juan Carlos Ramı́rez; Guido Mastrantonio; Alejandro G. Schijman; Jaime Altcheh; Adelina Riarte; Facundo García‐Bournissen (2016)
Pharmacological treatment of Chagas disease with benznidazole (BNZ) is effective in children in all stages, but it is controversial in chronically infected adults. We report the pharmacokinetics and pharmacodynamics in six adult patients with Chagas disease treated with the new BNZ formulation (ABARAX®) in doses between 2.5-5.5 mg/Kg/day. All but one patient had plasmatic BNZ concentrations within the expected range. All patients finalised treatment with nondetectable Trypanosoma cruziquantitative polymerase chain reaction, which remained nondetectable at the six month follow-up. Our data suggests parasitological responses with the new BNZ and supports the hypothesis that treatment protocols with lower BNZ doses may be effective.